2016
DOI: 10.5005/jp-journals-10024-1904
|View full text |Cite
|
Sign up to set email alerts
|

Work-related Musculoskeletal Pain among Different Dental Specialists in United Arab Emirates

Abstract: The prevalence and distribution of musculoskeletal disorders (MSDs) among registered general dental practitioners and dental specialists in UAE was not clearly documented. The study results indicated that the region that experienced musculoskeletal pain does vary according to the specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…In the present study, around 51% of dentists reported MSP in more than one region, and 30% of dentists reported MSP in only one region. This is in accordance with another study conducted in the UAE, 11 which found that 67% of dentists across the Emirates suffer from MSP, with chronic, dull pain being the most common. Furthermore, both the present and the earlier study found that the most common regions of pain were the lower back and neck region.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, around 51% of dentists reported MSP in more than one region, and 30% of dentists reported MSP in only one region. This is in accordance with another study conducted in the UAE, 11 which found that 67% of dentists across the Emirates suffer from MSP, with chronic, dull pain being the most common. Furthermore, both the present and the earlier study found that the most common regions of pain were the lower back and neck region.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that the use of magnification tools during dental work has a positive impact on the dentist’s posture and on minimizing MSP. The results of our study aligned with those of Aghilinejad et al ,[ 6 ] Al-Rawi et al ,[ 20 ] and Lietz et al . [ 14 ]…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the relation of back pain with the different specialties in dental field, our study agrees with the Al-Rawi N. et al (14) ,who concluded that the incidence of back pain is related to specialty.…”
Section: Discussionsupporting
confidence: 92%